Mendidik Perilaku Koruptif Berdasarkan Ibrani 13:5 - Romelus Blegur; Nico Pabayo Gading; Sonya Debora Atty (Didache: Journal of Christian Education, 2022)
The focus of this research is on corruption as a global and serious problem that causes unrest in various parts of the world. The impact is so serious and dangerous for the existence of a nation that it attracts a lot of attention and efforts to deal with it. Amid these efforts, this study aims to provide an ethical-theological offer and answer to educate corrupt behavior by referring to the text of Hebrews 13:5. The method used in this research is a literature research and hermeneutic study. The result of this research is that to prevent corrupt behaviour, character education is needed as a step to form good behaviour. In addition, efforts are needed to cultivate satisfaction to avoid greed that has the potential to encourage acts of corruption. This research offers a God-centered education as an ethical-theological basis that guarantees the fullness of human life and allows a person not to behave corruptly.